APPLICATION OF THE ROLE PLAYING LEARNING MODEL TO IMPROVE CLASS VII STUDENT'S ENGLISH LEARNING OUTCOMES SMP NEGERI 1 WONGSOREJO ODD SEMESTER ACADEMIC YEAR 2021/2022 - Pradana, Dian Arief; Rohmah, St.Shabibatul; Arifqi, Adenia Lutfany (Nusantara Hasana Journal, 2022)
Teaching and learning activities are a condition that is deliberately created. It is the teacher who creates it to teach students. Teachers who teach and students who learn. The combination of these two human elements creates an educative interaction by utilizing materials as the medium. There, all teaching components are played optimally in order to achieve the teaching objectives that have been set before teaching is carried out. The Role Playing Learning Model is a way of mastering lesson materials through the development of imagination and appreciation that is carried out by students by playing as story characters. Learning outcomes are increased changes in abilities possessed after someone follows the learning process. Learning outcomes achieved or achieved by students that reach the psychological realm of students which include (Cognitive, Affective, and Psychomotor). So learning with role playing is a way of learning that is done by dividing into several groups and each group playing a character according to the script made and the material that has been determined by the teacher, so that students more easily understand and remember the material that has been played. In this study, student activities support and support teacher activities in the application of the role playing learning model. Student activities are the main factors that play an important role in improving learning outcomes in the three domains, student activities, teacher activities, and improving student learning outcomes are three interrelated things. Results Based on the research and discussion, data obtained from student learning outcomes, namely getting an increase from before cycle 75%, Cycle I 81.2% and Cycle II 93.8% of the classical completeness target of 90%, it can be said if the Implementation of the Role Playing Learning Model can Improving Learning Outcomes of English Subjects for Class VII Students of SMP Negeri 1 Wongsorejo Odd Semester for the 2021/2022 Academic Year.